Dampak Psikologis Banjir Terhadap Siswa Di SMAN 1 Karanganyar Demak: Sebuah Studi Analisis Wacana Kritis Artikel Detiknews, "11 Kecamatan Di Demak Banjir Imbas 6 Tanggul Jebol, 93 Ribu Jiwa Terdampak" Dengan Pendekatan Norman Fairclough - Eny Junyanti (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The flood that hit Demak district in February 2024 has had a major impact on the life of SMAN 1 Karanganyar students. The aim of this study is to see how the flood affects the psychology of students, as described in the article titled "11 districts in Flood Demak Imbas 6 Tanggul Jebol, 93 Thousand Souls Affected". The study uses critical discourse analysis (CDA), which is combined with the Norman Fairclough approaches.The results show that the flood has caused a variety of psychological impacts on students, including anxiety, depression, and trauma. Anxiety is marked by fear, anxiety, and restlessness because of the possibility of flooding happening again. Trauma and depression are marked by bad memories and flashbacks about flood events. According to the analysis carried out in the article detiknews, the flood was described as a tragic and sad event. In this article, words like "burst," "affected," and "displaced" are used to describe unstable circumstances. Besides, photos showing the damage caused by the flood are included. The psychological consequences of the victims, however, are not much mentioned in the articles of DetikNews. This article only mentions that floods can cause trauma and stress, but does not discuss how these psychological impacts can affect students' lives, such as their social relationships and learning outcomes. This study suggests that it is important to pay attention to how flooding affects students' psychology.